Design and Implementation of Reliable Voltage Level Shifter Using Different Current Mirroring Phenomena - D. Venkanna Babu; Dr. Kiran Kumar Gurrala; Sanath Kumar Tulasi; P. Tejasri; Ch. Saranya; K. Jaya Varma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The project focuses on creating a reliable voltage level shifter through the implementation of various current mirror topologies in VLSI technology. Current mirrors, known for their precision in copying currents between transistors, offer versatile circuit configurations for biasing, current scaling, and power management. By leveraging the unique properties of different current mirrors, the suggested solution aims to enhance voltage shifting processes, reduce power dissipation, and improve circuit stability. Power has been decreased than the existed method. It has approximately obtained as 41.75µW for Cascode and 18.38µW for Wilson Current Mirrors. The real-world application of this design seeks to elevate the robustness and reliability of voltage shifting in electronic circuits. This design and implementation are performed in mentor graphics (EDA tool).
Keywords: Tanner EDA tool; Voltage level shifter; Cascode current mirror; Wilson current mirror; Robust Design; Voltage conversion; Topological Current Mirrors